GALAXITE, MnAl2O4, A SPECTROSCOPIC STANDARD FOR TETRAHEDRALLY COORDINATED Mn2+ IN OXYGEN-BASED MINERAL STRUCTURES - Hålenius U.; Bosi F.; Skogby H. (My University, 2007)
Chemical analyses, crystal structure refinement, cation order determination, and single-crystal optical absorption spectrum of synthetic galaxite are presented. New optical absorption spectra of natural Mn-bearing willemite, rhodochrosite, Mn-rich forsterite, and tephroite are reported for comparative purposes. The structure of a synthetic galaxite end-member is characterized by a relatively large unit-cell edge, αo = 8.2104(3) Å, a u-parameter equal to 0.26588(7), a T-O distance of 2.0034(6) Å, and an M-O distance of 1.9310(5) Å. Mn2+ is strongly ordered at the tetrahedral T-site as demonstrated by the refined structural formula T(Mn0.92+ 0Al0.10)M (Mn0.102+0 Al1.90)O4. The optical absorption spectrum of galaxite in the range 300-800 nm shows a set of five relatively sharp bands at 20 300, 22 250, 23 390, 25 970, and 27 780 cm-1 marking spin-forbidden transitions in Mn2+ at the tetrahedral site. The molar absorption coefficient of the field-independent 6A1(S) → 4Eg 4A1g(G) absorption band at 23 390 cm-1 equals 1.90 L/(mol·cm), which is approximately an order of magnitude higher than for corresponding bands in spectra of compounds that contain isolated Mn2+ -centered octahedra. The calculated crystal field splitting, 10Dq, for Mn2+ at the T-site in galaxite equals 5290 cm-1. This compares well with derived 10Dq-values of 5860 and 5510 cm-+ for Mn2+ at the tetrahedral T1- and T2-site in Mn-bearing willemite. In agreement with theory, the 10Dq for Mn2+ in MnO4 tetrahedra is ca. 30% smaller than corresponding values in MnO6 octahedra. The lower Racah B-parameters of the spectroscopic data indicate that the degree of covalency of Mn2+ -O bonds is higher in tetrahedra than in octahedra.
Keywords: CRYSTAL STRUCTURE; FORSTERITE; GALAXITE; OPTICAL SPECTROSCOPY; TEPHROITE; WILLEMITE